Rancang Bangun Host Sistem Mini SCADA Untuk Pengontrolan Beban Trafo 20 KV Pada Gardu Induk - Ikhwanto Ikhwanto; R.A Suwodjo Kusumoputro; Novi Azman (Jurnal Ilmiah Giga, 2014)
In this era of globalization, the needs of remote control systems isincreasing, where the system used is more sophisticated. Similarly, when a transformeroperator in electrical substations, which will control and monitor the load transformer 20KV is still done by hand. This will result in less efficient and optimal performance of theoperator. We need a system that can control remotely. To overcome these problems, hencedesigned "Host Mini SCADA systems for controlling the load on 20 KV transformersubstations parent. With this system an operator can perform control and monitoring of theload transformer 20 KV, among others: Frequency, Current, Voltage, and Temperature. Inaddition, this system also can detect if the transformer is faulty. Monitoring and controllingperformed remotely via SMS Gateway. This system consists of a PC (Personal Computer),which functions as process control and remote control units. GSM Modem serves to makethe process of data transfer via SMS (Short Message Service). Software Visual Basic, aprogramming language used to create a program / software on Host mini SCADA system.